Leveraging digital platforms for disseminating health and nutrition information during COVID-19: reflections from Project *Samvad* in India - Farhad Ali; Sanjay Kumar Paswan; Gelsey Bennett; Ronali Pradhan; S B Nadagouda; Sanjukta Roy Choudhury (Inishmore Laser Scientific Publishing Ltd, 2021)
Countries around the globe, including India, are making strides to combat maternal and child health issues. To support these efforts, Digital Green implemented Project *Samvad*, a USAID-funded reproductive, maternal, newborn, and child health (RMNCH) project working across six states in India. The project used a human-mediated community video approach to improve maternal and child health outcomes. In early 2020, due to mobility-related restrictions and norms related to physical distancing resulting from the COVID-19 pandemic, Project *Samvad*'s field activities stalled. This descriptive study highlights the project's pivot to the use of digital tools to reach beneficiaries during the COVID-19 pandemic. The project delivered COVID-19 related information by layering it on the existing RMNCH messages. It used WhatsApp and Interactive Voice Response System to reach out to the community and frontline workers. The content of the messages was locally relevant, culturally appropriate, and addressed the concerns of the local community concerning their immediate needs related to RMNCH and COVID-19. The project recorded a listenership of 85,199 and a content viewership of 283,866 in three months. The initiative also oriented 918 frontline workers virtually on their roles and responsibilities during COVID-19. The insights from the adaptation of our approach in the context of COVID-19 can help project managers and policymakers address communication issues during the pandemic or any other emergency, using digital dissemination for reaching beneficiaries, building the capacities of partners, engaging community members and frontline workers for improved learning, and dealing with process-related challenges.